2016
DOI: 10.18632/oncotarget.12041
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin potentiates the effect of arsenic trioxide against human hepatocellular carcinomain vitroandin vivo

Abstract: Hepatocellular carcinoma (HCC) is a highly lethal malignancy mostly because of metastasis, recurrence and acquired resistance to conventional chemotherapy. Arsenic trioxide (ATO) is successfully used to treat hematological malignancies, and has been proven to trigger apoptosis in HCC cells. However, the phase II trial evaluating the efficacy and toxicity of ATO in patients with HCC showed that single-agent ATO is poorly active against HCC. Therefore, it is of great importance to develop effective chemosensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…40 Similar reports had been reported in liver cancer. 41 The above studies provided ideas for the combination of SK and other anti-hepatocarcinoma drugs. In the present study, we evaluated the combined effects of SK and sorafenib both in vitro and in vivo experiments.…”
Section: Discussionmentioning
confidence: 95%
“…40 Similar reports had been reported in liver cancer. 41 The above studies provided ideas for the combination of SK and other anti-hepatocarcinoma drugs. In the present study, we evaluated the combined effects of SK and sorafenib both in vitro and in vivo experiments.…”
Section: Discussionmentioning
confidence: 95%
“…Shikonin, a natural naphthoquinone derived from the Chinese medicinal herb Lithospermum erythrorhizon, showed synergistic effect with gemcitabine, cisplatin and arsenic trioxide against pancreatic [95], colon [97] and hepatocellular [98] cancer, respectively. Song et al [28] and Liu et al [36] have also demonstrated the chemosensitizing effect of oxymatrine, one of the major components extracted from Sophora flavescens, widely used in TCM.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies about ATO focused on combination treatment with other drugs, such as icariin, metformin, shikonin, sorafenib. The results showed that combined treatments with ATO potentially enhanced the antitumor effect in HCC (27)(28)(29)43,44). There was study showed that ATO induced mitochondrial apoptotic cell death by ROS increase which was potentially required for activations of p38 MAPK and JNK in human cervical cancer cells (18,28,43).…”
Section: Discussionmentioning
confidence: 95%
“…The results showed that combined treatments with ATO potentially enhanced the antitumor effect in HCC (27)(28)(29)43,44). There was study showed that ATO induced mitochondrial apoptotic cell death by ROS increase which was potentially required for activations of p38 MAPK and JNK in human cervical cancer cells (18,28,43). Notably, metformin synergized with ATO inhibited proliferation of intrahepatic cholangiocarcinoma cells potentially via promoting cell apoptosis and regulating AMPK/p38 MAPK-ERK3/mTORC1 pathways (45).…”
Section: Discussionmentioning
confidence: 98%